2012
DOI: 10.1002/wsb.217
|View full text |Cite
|
Sign up to set email alerts
|

Modeling vaccination and targeted removal of white‐tailed deer in Michigan for bovine tuberculosis control

Abstract: White-tailed deer (Odocoileus virginianus) in Michigan, USA, is one of the few species in the world considered a maintenance host for bovine tuberculosis (TB). Prevalence of TB over the past decade has remained steady in Deer Management Unit (DMU) 452 and new control strategies are needed to further reduce prevalence or eradicate the disease. There is little public support for large-scale culling of deer in Michigan, and vaccination is being considered as a potential management tool. Our goal was to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Across the three different mechanisms, negative covariation decreased maximum prevalence, increased time to reach maximum prevalence, and dampened the rate at which the disease spread through the population relative to all other types of covariation. Universally, differences between types of covariation were strongest for theoretical pathogens with lower transmission efficiency, which suggests that such heterogeneity may be most important for less infectious, more chronic diseases in wildlife such as bovine tuberculosis (Cosgrove et al 2012). This finding is consistent with studies using empirically informed networks that have found dynamic interactions to be more important at lower transmissibility (Chen et al 2014, Springer et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Across the three different mechanisms, negative covariation decreased maximum prevalence, increased time to reach maximum prevalence, and dampened the rate at which the disease spread through the population relative to all other types of covariation. Universally, differences between types of covariation were strongest for theoretical pathogens with lower transmission efficiency, which suggests that such heterogeneity may be most important for less infectious, more chronic diseases in wildlife such as bovine tuberculosis (Cosgrove et al 2012). This finding is consistent with studies using empirically informed networks that have found dynamic interactions to be more important at lower transmissibility (Chen et al 2014, Springer et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…A combined field feasibility and modelling study of a live‐trap/test/cull or vaccinate approach suggested that 30 years of application in DMU 452 would cost ∼US$50 million and carry only a 34% probability of bovine TB eradication from white‐tailed deer (Cosgrove et al. 2012a, b). Consequently, mass distribution of oral baits is likely to be necessary.…”
Section: Vaccinationmentioning
confidence: 99%
“…Recent epidemiological models suggest that once M. bovis is introduced, the probability of becoming established in a wildlife population is at least 10% [104]. Furthermore, once established M. bovis can be fiscally impossible to eradicate, recent analysis found that to achieve eradication in Michigan would cost at least US $1.5 million annually over the next 30 years [105]. As a result identification and rapid response when M. bovis is transmitted from livestock to wildlife has proven the most successful tool for preventing establishment of M. bovis in wildlife [33].…”
Section: Opportunities For Management Of M Bovis In Wildlifementioning
confidence: 99%